A compact dual‐band zeroth‐order resonator antenna loaded with meander line inductor. Issue 7 (27th March 2020) - Singh, Monika; Kumar, Navneet; Dwari, Santanu; Parthasarathy, Harish; Kala, Pradyot
Abstract: A novel zeroth‐order resonator (ZOR) meta‐material (MTM) antenna with dual‐band is suggested using compound right/left handed transmission line as MTM. In this article, suggested antenna consists of patch through series gap, two meander line inductors, and two circular stubs. The MTM antenna is compact in size which shows dual‐band properties with first band centered at 2.47 GHz (2.05‐2.89 GHz) and second band is centered at 5.9 GHz (3.70‐8.10 GHz) with impedance bandwidth of ( S 11 < − 10 dB) 34.69% and 72.45%, respectively. At ZOR mode (2.35 GHz), the suggested antenna has overall dimension of 0.197 λ o × 0.07 λ o × 0.011 λ o with gain of 1.65 dB for ZOR band and 3.35 dB for first positive order resonator band which covers the applications like Bluetooth (2.4 GHZ), TV/Radio/Data (3.700‐6.425 GHz), WLAN (5‐5.16 GHz), C band frequencies (5.15‐5.35, 5.47‐5.725, or 5.725‐5.875 GHz) and satellite communication (7.25‐7.9 GHz). The radiation patterns of suggested structure are steady during the operating band for which sample antenna has been fabricated and confirmed experimentally. It exhibits novel omnidirectional radiation characteristics in phi = 0° plane with lower cross‐polarization values.